PENGARUH STRATEGI PROMOSI MELALUI SOCIAL MEDIA (Context, Communication, Collaboration, Connection) TERHADAP MINAT BELI KONSUMEN (Studi Kasus pada Produk Pakaian Old Man Store di Semarang) - susetyarsi, theresia; Herminingtyas, Rudika (Sekolah Tinggi Ilmu Ekonomi Semarang, 2021)
This study aims to determine how the influence of promotional strategies through social media (context, communication, collaboration and connection) on consumer buying interest in Old Man Store Semarang. To answer the research objectives, so a research was conducted by taking as many as 80 samples of consumers who live in the city of Semarang. The method use in sampling is non probability sampling method, namely sampling by determining specific criteria for consumers in the city of Semarang. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used multiple linear regression analysis and the data were processed using SPSS software version 17 for windows. Based on the results of the analysis, it is shown that the context variable has a positive effect on buying interest, namely 0,666, the collaboration variable has a positive effect on consumer purchase intention, which is equal to 0,305 connection has a positive effect on customer buying interest, namely 0,267. Meanwhile, the communication variable has a negative effect on consumer purchase interest, which is -0,004. Variables simultaneously or together variables context, communication, collaboration and connection have an effect on buying interest in Old Man Store of 30,139 with a significance value of 0,000. Variable context, communication, collaboration dan connection explain the variable consumer buying interest in Old Man Store Semarang at 61,6% while the remaining 38,4% is explained by other causes outside the model